(3GdLRA GdKGfjs - (3GSeGYjd jMj(B, (3GdJcQjJjs; (3YHO GdhgGH MHT GdWYeI(B, (3GfJUGQ YHhO eQGO GdJejejs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2010)
(3GdfbOjI h GdQbGHI YdjgG , GdeOjfhf h cd eG jJYdb HgPG GdGUd eTjQjf Edi GdOjhf GdeTchc aj JMUjdgG h WQb eYGdLJgG , ChQGb GdbHV GdJj JMUd YdjgG GdhMOI GdGbJUGOjI efGdeOjfhf h cjajI eYGdLJgG eMGSHjG h cd eG jJYdb HgPG GdHfO ef HfhO GdGUhd GdeJOGhdI ,GdGSJKeGQGJ GdeGdjIbUjQI GdGLd ef CSge h SfOGJ h CSGdjH eYGdLJgG h HeG jJab eY GdeYGjjQ GdeMGSHjI, GdeNRhf GdSdYj ef hLgI fXQ GdQbGHI Ydjg h JMOjO JcdaJg ShGA cGf HGdLQO GdOhQj Ce HGdLQO GdeSJeQ, GdGUhd WhjdI GdGLd , GdGdJRGeGJ bUjQI GdGLd (B.s
(3GdcJGH eMce JMcjeG YdejG h efgLjG ; eQGLY U(B.311s
Keywords: (3GdGSJKeGQGJ GdeGdjIs; (3GdeMGSHI GdeGdjIs; (3JObjb GdMSGHGJs